Major adverse cardiac and cerebrovascular event and patients' quality of life after endoscopic vein harvesting as compared with open vein harvest (MAQEH): a pilot study. Issue 1 (9th January 2018) - Luckraz, Heyman; Cartwright, Carly; Nagarajan, Kumaresan; Kaur, Prabhjeet; Nevill, Alan
Abstract : Background: This is a prospective, comparative, pilot and follow-up (2-year postoperatively) study in patients undergoing coronary artery bypass graft surgery where the long saphenous vein was harvested either by the endoscopic vein harvest (EVH) technique or open vein harvest (OVH) technique. Quality of life (QOL) and major adverse cardiac and cerebrovascular events (MACCE) were assessed. Methods: Alive patients who were initially part of a pilot study when EVH was introduced in our institution were included (n=48 EVH, n=49 OVH). Patients were sent a QOL questionnaire (SF12v2; 12-item medical outcomes study short form health survey version 2.0), and their cardiologist and general practitioner were contacted to assess MACCE. Results: Median follow-up was 32 and 33 months, respectively. Three patients died (2 EVH, 1 OVH). Of the remaining 97 patients who were sent a questionnaire, 76% patients returned the form. More patients from the EVH group returned the QOL questionnaire (82% vs 71%). Time taken to return to normal daily activities was much shorter in EVH (median 6 (2–30) weeks) compared with OVH (median 9 (2–50) weeks) (P<0.05). QOL questionnaire revealed significant difference in physical score at follow-up: 45.3 (10.2) for EVH group and 40.7 (11.0) for OVH group (P<0.05). There was no difference in mental scores (46.9 (10.5) vs 49.2 (9.1), P=0.4). There were no significant differences in MACCEs including death between the two groups (12.2% vs 13.9%, P=0.5). Conclusion: EVH patients returned to normal daily activities faster than OVH patients and experienced better physical QOL even after 2 years postoperatively with no increase in MACCE during follow-up.